New Structures Based on the Mixed Valence Polyoxometalate Cluster [V 12b18o60h6]N- - Costamagna-Martra, J; Costamagna-Martra, J; Venegas-Yazigi, D; Venegas-Yazigi, D; Hermosilla-Ibanez, P; Hermosilla-Ibanez, P (2012)
Hydrothermal synthesis was used to obtain four new crystalline lattices derived from the functionalization of the [V12B18O 60H6]n- cluster: Na8(H 3O){[Ni(H2O)5][V12B 18O60H6]}·12.5H2O (1), Na5 (H3O)4{[Ni (H2O) 3(en)][V12B18O60H 6]}·9H2O (2), and Na9(H 3O){Zn0.5[V12B18O60H 6]}·11H2O (3), [Hen][H2en]{[Zn(en) 2]3 [V12B18O60H 6]}·3H2O (4). All four compounds crystallize in the space group C2/c. Compounds (1) (2) and (4) are 0D species, while for (3) there is some degree of covalent connectivity between the anionic units, due to the presence of ZnII cations with partial occupation between them. On the basis of structural data and BVS calculations, these functionalized cluster species present mixed-valence ratios of 11VIV/1VV for (1), (2) and (3) and 9VIV/3VV for compound (4). Compounds (1), (2) and (3) present sodium and hydronium ions in the crystalline lattice, while protonated ethylenediamine is observed in compound (4). These cations balance the negative charge of the corresponding clusters and stabilize the crystalline lattice by electrostatic interactions. In the studied compounds, NiII ions coordinate to the vanadyl oxygen atoms, whereas the ZnII cations coordinate both to the vanadyl oxygen atoms and to the oxygen atoms bonded to boron centres. The electronic spectra in the low energy range are dominated by the IVCT phenomenon, since the functionalization of the cluster [V12B18O60H6]n- by different transition metal ions does not affect the observed absorption bands. © 2012 The Royal Society of Chemistry.